A novel method of growing fungi for DNA extraction - Keith A. Seifert (Fungal Genetics Reports, 1994)
Preparation of fungi for DNA extraction typically involves growing cultures in liquid culture in Erlenmeyer flasks, Roux bottles or even microfuge tubes (Cenis 1992 Nucl. Acids Res. 20:2380). Growing fungal cultures in liquid may require formulating new media or determining aeration requirements, and there are no rapid means of confirming the identification of the resulting mycelium. Fungi are grown routinely on agar media for identification, but agar complicates DNA extraction.